Apatite fission track geochronology of the Southern Hunan province across the Shi-Hang Belt: insights into the Cenozoic dynamic topography of South China. Issue 8 (11th June 2017) - Su, Jinbao; Dong, Shuwen; Zhang, Yueqiao; Li, Yong; Chen, Xuanhua; Li, Jianhua; Cui, Jianjun; Chen, Jiansheng
ABSTRACT: The Shi-Hang Belt is a Mesozoic tectonic zone and has always been regarded as the boundary between the Yangtze and Cathaysia blocks. It occupies a key tectonic location and attracts considerable attention due to its dynamic formation mechanism. However, its Cenozoic dynamic process is poorly constrained. The Cenozoic activation of the Shi-Hang Belt, as well as its cooling and exhumation, aids in dating the onset time of the formation of the mountain ranges and reveals the deformation process of the South China Block. To uncover the history of its Cenozoic cooling and denudation, apatite fission-track (AFT) thermochronology was applied to batholiths and strata spread across the Shi-Hang Belt in the Hunan Province. Twenty-three samples are dated with ages ranging from 23.6 ± 1.5 to 45.8 ± 3.0 Ma. Except for two older ages (42.1 ± 2.6 and 45.8 ± 3.0 Ma), the other ages range from 23 to 36 Ma with less variation on both sides of the Chenzhou–Linwu fault. The thermochronological modelling of 15 measured samples demonstrates that rocks rapidly passed through the AFT partial annealing zone to the near surface at different onset times from 36 to 23 Ma. The regional AFT cooling pattern is unrelated to the internal structures of the Shi-Hang Belt characterized by a Mesozoic fold-thrust feature. We attribute the Cenozoic exhumation of the Shi-Hang Belt to the dynamic topography of the South China Block, which is related to mantle downwellings and upwellings due to several episodes of quick subduction of the Pacific Plate underneath Eurasia during the Late Cretaceous–early Cenozoic and the Oligocene–early Miocene. The far-field effect of the India–Tibet collision may have contributed to the exhumation of the Shi-Hang Belt.